Qu’est-ce qu’une politique de traduction ? - Julie Abbou; Katy Barasc; Cornelia Möser; Manuel Perez (Glad!)
The Translation Committee of the Journal GLAD! offers to develop a politics of translation, in order to discuss and connect the political, theoretical and practical aspects of translation in a feminist journal.